Development of the standard mouse model for human bacterial vaginosis induced by Gardnerella vaginalis - Kwak, Jinok; Pandey, Sriniwas; Cho, Jinho; Song, Minho; Kim, Eun Sol; Doo, Hyunok; Keum, Gi Beom; Ryu, Sumin; Choi, Yejin; Kang, Juyoun; Kim, Sheena; Kim, Jeongyun; et al. (Frontiers in Veterinary Science, 2023)
Bacterial vaginosis (BV) is a polymicrobial syndrome characterized by a diminished number of protective bacteria in the vaginal flora. Instead, it is accompanied by a significant increase in facultative and strict anaerobes, including Gardnerella vaginalis (G. vaginalis). BV is one of the most common gynecological problems experienced by reproductive age-women. Because an ideal and standard animal model for human BV induced by G. vaginalis is still underdeveloped, the main objective of this study was to develop a mouse model for human BV induced by G. vaginalis to demonstrate the clinical attributes observed in BV patients. A total of 80 female ICR mice were randomly assigned to 4 groups and intravaginally inoculated with different doses of G. vaginalis: NC (uninfected negative control), PC1 (inoculated with 1 x 105 CFU of G. vaginalis), PC2 (inoculated with 1 x 106 CFU of G. vaginalis) and PC3 (inoculated with 1 x 107 CFU of G. vaginalis). The myeloperoxidase (MPO) activity and serum concentrations of cytokines (IL-1β, IL-10) in mice administered with G. vaginalis were significantly higher than those of the control group. Gross lesion and histopathological analysis of reproductive tract of mice inoculated with G. vaginalis showed inflammation and higher epithelial cell exfoliation compared to the control group. In addition, vaginal swabs from the mice inoculated with G. vaginalis showed the presence of clue cells, which are a characteristic feature of human BV. Altogether, our results suggested that G. vaginalis is sufficient to generate comparable clinical attributes seen in patients with BV.